Timing should no Longer be an Obstacle to Oocyte Cryopreservation in Patients with Cancer. Issue 2 (March 2017) - Mangili, Giorgia; Papaleo, Enrico; Sigismondi, Cristina; Masciangelo, Rossella; Sarais, Veronica; Giorgione, Veronica; Nale, Roberta; Privitera, Laura; Carnelli, Letizia; Di Mattei, Valentina; Candiani, Massimo
Purpose: Anticancer treatment-related infertility is preventable with oocyte cryopreservation, but this is often not considered a relevant issue, due to lack of knowledge and time. The aim of this study is to prove that adequate organization of an Oncofertility Unit and the use of new protocols for controlled ovarian stimulation (COS) can reduce the time required by the procedure, encouraging consultants and patients to preserve fertility before gonadotoxic treatments. Methods: A total of 125 patients diagnosed with malignant tumors were referred to the Oncofertility Unit of San Raffaele Hospital: 52 patients between April 2011 and October 2013 and 73 patients between October 2013 and November 2015. The 2 periods differ in office organization and type of COS protocol used. Results: Between the 2 periods, a reduction in the mean number of days required from first counseling to the initiation (6.45 ± 1.058 vs 1.61 ± 0.228) and the end of the COS (17.83 ± 1.227 vs 13.70 ± 0.393) was observed (p<0.0001). No differences exist in the groups between the mean time required to complete COS (11.38 ± 0.360 vs 12.17 ± 0.309; p = 0.11) and mean number of frozen oocytes (8.458 ± 1.060 vs 10.30 ± 0.919; p = 0.22). Furthermore, in the second period, the number of patients who accepted fertility preservation increased (46.15% vs 64.38%; p<0.05). Conclusions: Renewed organization of the Oncofertility Unit and the newest random-start COS protocol allowed us to shorten the time for oocyte cryopreservation and start anticancer treatment on time.